Protocol Adherence in the Intensive Care Unit for the Management of Adult Patients Admitted with Acute Aneurysmal Subarachnoid Hemorrhage - Taylor, Lily; Lane, Andrew S. (Journal of Neuroanaesthesiology and Critical Care, 2021)
Background There are recognized protocols that exist for management with minimal data regarding protocol adherence. We conducted a retrospective analysis of aneurysmal subarachnoid hemorrhage (aSAH) to determine whether the level of protocol adherence varied based on patient demographics or specific aspects of management.Materials and Methods All cases of aSAH admitted to a tertiary-level intensive care unit (ICU) from 2014 to 2016 were identified from the Australia and New Zealand Intensive Care Society Core Database as well as the clinical records system. ICU demographic and descriptive data for protocol adherence, were collected from admission to discharge up to 22 days, or until death whichever was earlier.Results A total of 58 cases of aSAH were registered; mean age was 56.7 years, 70.7% of patients were female, and mean length of stay was 12.6 days. World Federation of Neurosurgical Societies (WFNS) scale was documented more than Fisher grading. Of the 58 cases, 63.7% (37) underwent surgical clipping, with 83.7% (30) patients having this surgery within 48 hours. SBP/MAP were the most consistently recorded observations within protocol ranges, with adherence of 82.4% and 82.1%, respectively. Thirty-two percent of temperature measurements were outside of the normothermic range of 36.5 to 37.5°C with a mean adherence of 47.5% (standard deviation = ±0.24, median = 40). There was no correlation between adherence and patient, disease, or admission factors.Conclusion This study demonstrated that there was no association between variation in protocol adherence based on age, admission dates, or disease factors including WFNS grade and Fisher scale. Best protocol adherence protocol for the management of aSAH within the ICU was blood pressure control. Areas for improvement were documentation of the WFNS and Fisher grading, and temperature measurement and management.
Keywords: acute aneurysmal subarachnoid hemorrhage; blood pressure control; protocol adherence